The Impact of Level of Education of Pregnant Women on Nutritional Adherence - Bada, Festus Olatunji; Falana, Bernard Akinlabi (Mediterranean Journal of Social Sciences, 2012)
The study examined the impact of educational level of pregnant women on their adherence to nutrition recommendation inAdo-Ekiti local government area of Ekiti state. The study investigated the Impact of education, the knowledge, the social status, socioeconomicand socio-cultural factors on adherence to nutrition among pregnant women in Ekiti State, Nigeria. The research design for thestudy was descriptive in nature and survey approach was adopted for the entire population. The population consisted of the literate andilliterate pregnant women of child bearing ages selected through purposive random sampling technique in five hospitals in Ado-Ekiti localGovernment. A sample of 100 respondents was randomly selected using purposive and stratified random sampling technique. Aquestionnaire tilled “Education and nutrition of pregnant women in Ekiti State “was used for collecting data. To ensure the validity of theinstrument copies of the instrument were given to health care practitioners and nutrition specialists in the hospitals that are not part of thesample and the Department of Health and Human kinetics Ekiti State University. They ensured face and content validities of theinstrument. A reliability coefficient of 0.74 was obtained using test retest reliability. This was found significant at 0.05 level of significance.The instrument was personally administered in the maternity homes in Ado-Ekiti local Government Area of Ekiti State. The datagenerated were analysed using descriptive and inferential Statistics. The general question raised was answered using frequency countsand percentages. The hypothesis postulated was tested using Chi-square (x2). The analysis of the data revealed that Educationdetermined to a large extent the nutritional adherence by pregnant women. There are significant relationship between the education levelof respondent pregnant women and their nutritional adherence. Based on the findings, the curriculum planners should integratenutritional counselling to all levels of education in Nigeria schools. The Ekiti State Government and Nigeria Government should have anutritional guide for would be pregnant women in Ekiti State.